Law of domestic rape: harmonisation between Shariah and Penal code - Mohamad Yunus, Mohamad Ismail (Royal Malaysia Police, 2011)
Under the definition of rape that is generally used by the courts, rape is “an act of non consensual sexual intercourse by a man with a woman other than his wife”. Under this commonly accepted definition it is not legally possible for a husband to rape his own wife. The husband cannot be liable as the principal offender based on the idea that consent to marriage is also consent to sexual intercourse which cannot be revoked while the marriage subsist. This paper will examine the law relating to marital rape according to Islamic law, Malaysian Penal Code and the contemporary arguments in favour and against the spousal immunity viewed by the modern secular legal jurists.